(untitled) (Journal of the College of Basic Education, 2025)
Makran played an important role in the Islamic East after the Islamic conquests of the region. It was conquered during the era of the Rashidun Caliphate during the reigns of the two Caliphs Omar bin Al-Khattab and Othman bin Affan (may Allah be pleased with them). The importance of the city is due to its geographical location as a point of contact between India, Persia and Iraq, in addition to its political role throughout the Islamic eras, the most important of which is that it is a stronghold and center of conflicts during the Umayyad era; and the Buyid conflict during the Abbasid Caliphate. Not to mention the city’s civilizational role through the population diversity of Persians, Indians and Arab Muslims who settled in the city after the conquest. The city is also a center for religious diversity, in addition to commercial and agricultural activity, and finally the intellectual movement, as the city produced a constellation of prominent scholars.